PANDALUNGAN AS A MEETING POINT: THE INTERACTION OF ISLAMIC ECONOMY AND DA'WAH IN LOCAL HISTORY - Mahfufatur Rosidah; Ahmad Halid (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
This study aims to examine the role of the Pandalungan area as a center of interaction between economic activities and the spread of Islamic da'wah in the perspective of local history. With a qualitative approach through historical studies, this research utilizes sources from literature, interviews with community leaders, and observations of historical sites. The findings of the study revealed that trade routes function as an effective means in the process of Islamization, where Muslim traders play the role of spreading da'wah through ethical business principles and social interaction. Da'wah in this community takes place culturally, adaptively, and without confrontation. The Pandalungan people integrated Islam into their local traditions, resulting in a distinctive and contextual form of Islam. The study emphasizes the importance of cultural- and economic-based da'wah strategies in the success of past Islamization, which remains relevant in the current situation.